The Development of Science E-Modules Based of Guided Inquiry to Improve Students' Critical Thinking Ability - Muzzazinah Muzzazinah; Meti Indrowati; Diska Evi Liana (Postgraduate, University of Mataram, 2022)
This type of research is development research that aims to determine the characteristics, feasibility and effectiveness of the guided inquiry-based respiratory system E-module to improve students' critical thinking skills. The development model used is research and development which refers to the Borg and Gall development model which has been modified and adapted to conditions in the field, which consists of nine stages, namely: Research and informing collecting, Planning, Develop preliminary form of product, Preliminary feed testing, Main product revision, Main field testing, Operational product revision, Operational field testing, E-module final product. The data analysis technique used is descriptive analysis which is used to describe the characteristics of the e-module to be developed, the feasibility analysis of the e-module based on the N-gain score obtained. The results of the N-gain test score in the control class, which is 0.65, are included in the medium category, while for the experimental class the average N-gain score of 0.78 is included in the high category. Based on these results, guided inquiry-based E-modules are very feasible to be used in learning and have proven effective in improving students' critical thinking skills